Normalized epistemic injustices and restriction of the agency of persons with disabilities - Hernández, Raynier; Revuelta, Beatriz (Acta Bioethica, 2024)
Epistemic injustices refer to those forms of unfair treatment that are related to the production, transmission, or use of knowledge by the subjects. The ethical-epistemic and socio-epistemic framework provided by these injustices is linked to themes that cross the main philosophical traditions such as pragmatism, phenomenology, and critical theory. These injustices are further intertwined with social and intellectual movements such as feminism, critical race theory, critical disability studies, and decolonizing epistemologies. However, there is a question that people with disabilities have not been sufficiently addressed. This article is positioned in the current debates on epistemic injustices and disability, and its purpose is to contribute the concept of "normalized epistemic injustices". Starting from the verification of the ways in which subjects with disabilities are oppressively recognized, as far from the "norm", it establishes that there are epistemic injustices associated with this identification. It proposes that normalized epistemic injustices occur at the intersection of two realms: a capacitist hermeneutic system and a constrained epistemic agency where at least three types of configurations are produced: non-agency; diminished epistemic agencies and epistemic agencies in resistance. Thinking about epistemic injustices considering the weight of "normality" in the constitution as subjects of people with disabilities allows us to recognize a critical situation of epistemic exclusion for some people, while others resist and fight to be understood in collective hermeneutical resources.